Talent identification and development model in Iranian athletics - Hadavi F.; Zarifi, A. (World Journal of Sport Sciences, 2009)
The main purpose of this study was to design a model for talent identification and development in Iranian athletes. This project aimed at addressing the problem of coaches to find the best children and youth for track and field by a multi-factorial modeling. This model can be utilized to explain the present status of the talent identification process and provide suitable suggestions to improve the results of athletic fields in international competitions. In terms of methodology, a descriptive-analytical and field study was used to randomly select expert coaches (n = 38) in Iran. A research-made questionnaire was used to collect the data and the experts confirmed its content validity as well as reliability (" ~ %) in a pilot study. The data were collected via six factors: motor ability, physiological, anthropometrical, psychological, sociological and cultural. The results of this research lead to a special model of Iranian track and field. This model has three phases (initial selection, general tests and special tests) with specific aims such as determining unsuitable children for athletic fields, determining the abilities of the youth for track and field and improving the special abilities required of athletes. Also, each phase has a special "input entrance" such as the main input, classical input, games input, free input and championship input. This model determined the age and time span of each phase and also emphasized those in charge of each phase.